Correction of room impulse response truncation based on a nonlinear decay model. (March 2018) - Ćirić, Dejan G.; Janković, Marko
Highlights: Calculation of the correction term based on the nonlinear decay model is analyzed. The model parameters are calculated through an LS optimization. Late decay should contain the decay range of about 5 dB above the truncation time. Allowable correction term deviation ranges from ±20% to 100% from the true value. The proposed procedure outperforms the reference one from the literature. Abstract: Serious effects of noise present in room impulse responses (RIRs) on evaluation of room acoustical parameters can be compensated by applying different methods. One of the preferred methods is based on the noise subtraction, RIR truncation and correction for truncation. This paper presents a procedure for calculation of the correction term that should be added to the backward integrated truncated RIR. The procedure can be applied in an automated way, and it is based on a nonlinear decay model consisting of an exponential decay plus stationary noise. Unknown parameters of the model are calculated by an optimization procedure where the model is fitted to the measurements. The proposed procedure for correction term calculation is tested on both synthesized and measured RIRs. The effects of the procedure parameters related to the RIR estimation range used for fitting the model to the measurements are analyzed. This procedure is compared with the one often applied in practice as a reference. The comparison shows that the proposed procedure outperforms the reference one. In addition, the impact of changing the correction term on the reverberation time estimation is investigated.